1991
DOI: 10.1002/aja.1001910102
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous decidual reactions and menstruation in the black mastiff bat, Molossus ater

Abstract: Uterine function was assessed histologically in nonpregnant Molossus ater removed from a laboratory breeding colony. During the luteal phase of the cycle, bilateral decidual reactions were found to develop spontaneously in the absence of either embryos or experimental manipulation of the uterus. These included the formation of early decidual giant cells, closure of the uterine lumina, and morphological changes in the endometrial blood vessels. Some endothelial cell hypertrophy was noted in much of the decidua,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…In women, menstruation is a unique form of tissue breakdown that occurs with each reproductive cycle and is followed by extremely rapid repair of the tissue without scarring (Salamonsen 2003). These events do not occur in other species with oestrous cycles, except to a limited extent in some old world primates (Finn 1987) and in a small number of bats (Rasweiler 1991;Rasweiler and de Bonilla 1992). One reason for this might be that, in women, decidualisation of the endometrial stroma occurs naturally during the late secretory phase of the cycle in preparation for implantation, whereas decidualisation only takes place in the presence of a blastocyst in other species with haemochorial placentation.…”
Section: Discussionmentioning
confidence: 97%
“…In women, menstruation is a unique form of tissue breakdown that occurs with each reproductive cycle and is followed by extremely rapid repair of the tissue without scarring (Salamonsen 2003). These events do not occur in other species with oestrous cycles, except to a limited extent in some old world primates (Finn 1987) and in a small number of bats (Rasweiler 1991;Rasweiler and de Bonilla 1992). One reason for this might be that, in women, decidualisation of the endometrial stroma occurs naturally during the late secretory phase of the cycle in preparation for implantation, whereas decidualisation only takes place in the presence of a blastocyst in other species with haemochorial placentation.…”
Section: Discussionmentioning
confidence: 97%
“…The reproductive biology of M. rufus has also been extensively studied under controlled conditions in captivity (Rasweiler, 1987, 1988, 1990a, b, 1991a, b, 1992, 1993; Badwaik et al, 1998), revealing this species to be an interesting model for studies of the biology of menstruation, trophoblastic growth and differentiation, and placental morphogenesis. During its menstrual cycle, M. rufus also exhibits, within its uterus, the most pronounced example of physiological (nonpathological) angiogenesis thus far observed in any adult mammal (Rasweiler, 1991a). Our description of the postimplantation embryology in M. rufus further advances the utility of this bat species for developmental studies.…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive biology of M. rufus has also been extensively studied under controlled conditions in captivity (Rasweiler, 1987(Rasweiler, , 1988(Rasweiler, , 1990a(Rasweiler, ,b, 1991a(Rasweiler, ,b, 1992(Rasweiler, , 1993Badwaik et al, 1998), revealing this species to be an interesting model for studies of the biology of menstruation, trophoblastic growth and differentiation, and placental morphogenesis. During its menstrual cycle, M. rufus also exhibits, within its uterus, the most pronounced example of physiological (nonpathological) angiogenesis thus far observed in any adult mammal (Rasweiler, 1991a). Our description of the postimplantation embryology in M. rufus further advances the utility of this bat species for developmental studies.…”
mentioning
confidence: 63%
“…These studies also revealed that the species is a spontaneous ovulator with a functional luteal phase to its cycle. The cycle is terminated by true menstruation (Rasweiler, 1988(Rasweiler, , 1991a.…”
Section: Timing Of Embryonic Developmentmentioning
confidence: 99%